Institutional framework for consumer credit Industry in Malaysia: learning from Australia, United Kingdom and South Africa - Hassan, Rusni; Ilias, Ibtisam @ Ilyana; Kassim, Salina; Abu Bakar, Elistina (Science and Engineering Research Support Society, 2019)
Financial consumers are not immune from exploitation, malpractices and oppressive treatment of financial service providers. In fact, they require greater protection than consumers of other types of goods and services for a variety of reasons. Prevailing problems endured by financial consumers are exacerbated by the absence of a single authority in Malaysian consumer credit industry to protect their rights and interests. This paper therefore scrutinizes the single institutional framework practised by three selected jurisdictions namely Australia , the United Kingdom and South Africa . The research concludes the viability of establishing a single institution to govern consumer credit industry . Necessary modification and arrangement however is pertinent to suit with the local circumstances. This new arrangement will benefit financial consumers in consumer credit industry by ensuring adequate and equal protection. Undoubtedly, strengthened financial consumer protection regime will increase market confidence and ultimately lead to financial stability and economic growth.